2015
DOI: 10.1007/s11661-015-3185-9
|View full text |Cite
|
Sign up to set email alerts
|

What is the Process Window for Semi-solid Processing?

Abstract: Abstract.In semi-solid processing, the liquid fraction versus temperature is commonly used to define the process window.Conventionally it is assumed a freezing range is required for semi-solid processing but recently both high-purity aluminium and binary Al-Si eutectic alloy have been rheo-processed. Here, the kinetics during melting and solidification of pure metal are analyzed and a comparison between the liquid fraction versus temperature and the liquid fraction versus time presented. It is found that liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…The small increase is also caused by a further reduction of the interaction between the surfaces. These values of the adhesive energy are smaller than the previous LDA value of 4.925 eV (1.660 J m -2 ) for the same GB [50], because the LDA tends to overestimate adhesive or cohesive energies compared to the GGA.…”
Section: Theoretical Methodscontrasting
confidence: 73%
“…The small increase is also caused by a further reduction of the interaction between the surfaces. These values of the adhesive energy are smaller than the previous LDA value of 4.925 eV (1.660 J m -2 ) for the same GB [50], because the LDA tends to overestimate adhesive or cohesive energies compared to the GGA.…”
Section: Theoretical Methodscontrasting
confidence: 73%
“…Processability of semi-solid alloys are affected by the size and morphology of primary particles as well as liquid fraction [169][170][171], so a sufficiently expanded solidus-liquidus interval and optimal liquid/solid ratio of the metal slurry are required traditionally.…”
Section: Evolution Of Non-dendritic Microstructural In Semi-solid Pro...mentioning
confidence: 99%
“…Processability of semi-solid alloys are affected by the size and morphology of primary particles as well as liquid fraction [169][170][171], so a sufficiently expanded solidusliquidus interval and optimal liquid/solid ratio of the metal slurry are required traditionally. The microstructural evolution in conventional solidification forms dendritic microstructure, which has been understood to include crystallization, solute redistribution, ripening, inter-dendritic fluid flow, and solid movement.…”
Section: Evolution Of Non-dendritic Microstructural In Semi-solid Pro...mentioning
confidence: 99%
“…Virtually, adding silicon into the wrought alloys can not only depress the temperature sensitivity significantly and reduce solidification shrinkage, but also improve the flowability, but with an inevitable decrease in mechanical behaviors. Surprisingly, inspired by the experiments by Curle et al on rheocasting of Al-Si binary eutectic alloy [40], pure Al [41], Zhang and co-workers [42] found that rheoforming can occur even there is no theoretical temperature interval between the solidus and liquidus because of the kinetics of solidification. Accordingly, for the wrought alloys, ideal slurry in which the primary particles are fine, spherical, and uniformly dispersed in the matrix can also be prepared if the solidification process is strictly controlled in spite of their higher temperature and enthalpy sensitivity.…”
Section: Possibility Analysis Of Slurry Preparationmentioning
confidence: 99%